THE EFFECTIVENESS OF THE RELOCATION PROGRAM FOR STREET VENDORS TO PURBALINGGA FOOD CENTER (PFC) AS AN EFFORT TO DEVELOP UMKM IN PURBALINGGA DISTRICT - Piani, Iin; Kusumaningtias, Eka; Ridwanca, Ardian (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The government has taken various initiatives to increase the value of culinary businesses, especially Micro, Small and Medium Enterprises (MSMEs), by localizing street vendors to culinary tourism centers. In Purbalingga Regency, the relocation of street vendors to the Purbalingga Food Center (PFC) was carried out by the government, but received various views from stakeholders because it did not fully meet the needs of the street vendors. This research aims to determine the effectiveness of the relocation program for street vendors to the Purbalingga Food Center (PFC) as an effort to develop MSMEs in Purbalingga Regency. Through a qualitative approach using interviews and observations, the research results show that even though the Purbalingga Food Center (PFC) is considered a culinary tourism destination, its success is still questioned by the public because it is not optimal in presenting culinary diversity, lack of local consumption, and inadequate supporting infrastructure. There is a need for harmony between the type of street vendor trade and existing facilities, as well as infrastructure improvements to ensure the effectiveness of the relocation policy. The government needs to focus efforts on increasing productivity enforcing strict regulations to support local economic goals. Therefore, the successful relocation of street vendors to the Purbalingga Food Center (PFC) as a symbol of the local economy requires better coordination between the government and business actors.